Analysis of Factors Influencing the BPJS Outpatient Registration System at Jati Husada General Hospital, Karanganyar - mumtaz, yasmin; Aqsyari, Rizki; Sriwiyati, Lilik; Andika, I Putu Juni (Jurnal Ilmu-Ilmu Kesehatan, 2026)
Digital transformation in the healthcare sector has driven the adoption of online outpatient registration systems to improve service efficiency and reduce patient queues. However, at Jati Husada General Hospital in Karanganyar, offline registration remains dominant for BPJS patients. This situation suggests factors influencing the choice of registration system. This study aims to analyze factors such as age, education, income, patient satisfaction, and service quality in the BPJS outpatient registration system. The study used a quantitative descriptive-analytical design with a cross-sectional approach. The population was 2,021 BPJS outpatient visits in March 2025, with a sample of 105 respondents selected using simple random sampling. Data were collected through questionnaires and analyzed using the Chi-Square test with a 95% significance level (α=0.05). The results showed that age (p=1.000), education (p=0.339), income (p=0.414), and service quality (p=0.109) did not significantly influence the outpatient registration system. Conversely, patient satisfaction had a significant effect (p=0.007). It is concluded that patient satisfaction is a factor that influences the outpatient registration system, so improving patient experience and comfort needs to be a priority in developing the service system. Keywords : Patient Satisfaction, Service Quality, Education, Income, Outpatient Registration System